2010
DOI: 10.1002/lary.20769
|View full text |Cite
|
Sign up to set email alerts
|

Septoplasty retards midfacial growth in a rabbit model

Abstract: These data demonstrate midfacial growth retardation after conservative septoplasty in young rabbits, and that this retardation could not be averted by replacing the resected cartilage with a porous polyethylene graft. These data are in agreement with human studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Animal models have suggested that bony septal resection before skeletal maturity significantly decreases facial growth. 23 However, Ortiz-Monasterio and Olmedo 24 demonstrated no detrimental effects in their longterm follow-up. Our current treatment plan for cartilaginous and bony septoplasty is to defer intervention until the time of full facial maturity.…”
Section: Discussionmentioning
confidence: 97%
“…Animal models have suggested that bony septal resection before skeletal maturity significantly decreases facial growth. 23 However, Ortiz-Monasterio and Olmedo 24 demonstrated no detrimental effects in their longterm follow-up. Our current treatment plan for cartilaginous and bony septoplasty is to defer intervention until the time of full facial maturity.…”
Section: Discussionmentioning
confidence: 97%
“…This observation was supported by the findings that the nasal septum responds to hormones and growth factors and has an intrinsic ability to grow. Additionally, extirpation of the nasal septum has been shown to impair midface development in rats and rabbits (10,36). However, such experimental approaches were criticized, as facial development is slower in humans than in the animal models used; thus, the observed midface malformations were attributed to surgical trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Sarnat 17 stated that the nasal septum is the facial growth-center and discussed various experimental surgical methods. Maxillofacial growth, particularly maxillary growth, is a multifac- torial process involving sutural growth, bone remodeling, and muscular interaction [18][19][20][21] . Many researchers now consider the nasal septum theory as the only logical interpretation ; growth of a jaw face by classi cation of the two-dimensional nasal septum form.…”
Section: Discussionmentioning
confidence: 99%